Allocating Resources for COVID-19 Recovery: A Comparison of Three Indicators of School Need. Issue 2 (3rd April 2022) - Schweig, Jonathan D.; McEachin, Andrew; Kuhfeld, Megan; Mariano, Lou; Diliberti, Melissa
ABSTRACT: As students return to in-person instruction in the 2021–2022 school year, local education agencies (LEAs) must develop resource allocation strategies to support schools in need. Federal programs have provided resources to support restart and recovery. However, there is little consensus on how LEAs can target resources to support those schools most in need. This study investigates the relationship between three school need indicators (i.e., pre-COVID student performance and progress, school and community poverty, and pandemic vulnerability) and measures of student performance and progress throughout the pandemic to determine which indicators support valid school need inferences. We find that school poverty more strongly predicts performance and progress during the pandemic than pre-COVID academic measures. In elementary schools, we find that pandemic vulnerability independently predicts achievement even when conditioning on poverty and pre-pandemic achievement. Of the indicators of poverty we investigated, the percentage of free and reduced-price lunch-eligible students is the strongest predictor.